PENTINGKAH KARAKTERISTIK PERUSAHAAN DAN TIPE INDUSTRI PADA PENGUNGKAPAN ANTI KORUPSI? - Ristiana Widianing Tyas; Isna Putri Rahmawati (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study aims to determine the influence of company size, industry type, and international operation on anti-corruption disclosures in non-financial companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The purposive sampling method is used to determine the sample in this study. This study has 170 observations with 85 companies. The content analysis method extracts the anti-corruption information in the sustainability report and annual reports. This study uses 12 checklist items from GRI 205 to measure the extent of anti-corruption disclosure. The analytical method used in this study is multiple linear regression. The results of this study indicate that company size and industry type have a positive and significant effect on anti-corruption disclosures. Meanwhile, international operations do not affect anti-corruption disclosures.